Anyway. Yeah, I know it's the same in this case, and I definitely know that's the purpose of it. I'm just saying the bit of code you gave didn't exactly translate to the piecewise function.

All in all, it doesn't talk about nested functions, because you can't do nested functions with piecewise, since everything get's compared. Imagine a case where my variable Q denoted whether I had initialized the list L1 yet. 1 being initialized, 0 being not initialized. If I did "X+Q(L1(1))->X" and L1 didn't exist, it would throw an error. However, if I do it in a nested if statement, the command to get L1(1) would never even be checked, and wouldn't throw an error..

]]>That's exactly what graphmastur put towards the end of his post. Nesting If/Then statements for doing only one command in between them is also an unnecessary use of memory. You could, like was stated, simply do

` ``If Q=3 and X=4 X+1→X`

or

` ``X+(Q=3 and X=4)→X`

Also, on a side note, you almost never need to use the multiplication sign because of the calculator's implicit multiplication.

]]>…

This is exactly the purpose of nesting If commands… We want to make sure that testing X=4 only happens if Q=3. If Q doesn't equal 3, we skip the next commands, and that's what happens when we use that piecewise syntax.

We could even replace the two If's by one and put Q=3 AND X=4, that'd really be the same.

Unless you'd want to use Else's or commands that don't imply variable changes, then it wouldn't be able to be turned into piecewise.

Thanks for the welcome.

]]>` ``If Q=3 : Then If X=4 : Then X+1->X End End`

This actually won't even test for X=4 if Q does not equal 3. What "X+1(Q=3)*(X=4)->X" translates to is this:

` ``If Q=3 and X=4 X+1->x`

Also note that you don't need the 1 in front of (Q=3). Also, I'm not sure on the timing of the instructions but (Q=3 and X=4) might be faster than multiplying the ones together.

So that's why it doesn't say anything about nesting if statements.

]]>Example :

If Q=3:Then:If X=4:Then:X+1->X:End:End

Can be replaced by

X+1(Q=3)*(X=4)->X

This is not intuitive when people don't know boolean logic or are confused by the line that says 'the statements must be mutually exclusive' in the concept part.

I do believe that the whole part has to be rewritten, honestly.